Review of the genus Salicarus (Hemiptera, Heteroptera, Miridae) - Fedor V. Konstantinov; Reza Hosseini (ZooKeys, 2024)
The genus Salicarus Kerzhner, 1962 is revised, with differential diagnoses and redescriptions provided for nine species. Three distinct species groups were recognized within the genus: S. nitidus group (S. cavinotum, S. genistae, S. nitidus, S. perpusillus), S. roseri group (S. concinnus, S. roseri, S. urnammu), and S. fulvicornis group (S. halimodendri, S. fulvicornis). A key to species, illustrations of dorsal habitus, male and female genitalia, and selected diagnostic structures are included. Additionally, available host information and distributional records are summarized. Phoenicocoris qiliananus Zheng, 1996 is synonymized with Salicarus halimodendri V. G. Putshkov, 1977.